2018
DOI: 10.3892/mmr.2018.9718
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B, an antioxidant derived from Salvia�militarize, protects mice against γ‑radiation‑induced damage through Nrf2/Bach1

Abstract: Salvianolic acid B (SB) is an antioxidant derived from Salvia militarize, and is one of the most widely used herbs in traditional Chinese medicine. SB is a potent antioxidant that has been well documented as a scavenger of oxygen free radicals, and has been used for the prevention and treatment of atherosclerosis-associated disorders. To explore its potential therapeutic effects in treating radiation damage, in this study, mice were treated with SB at different doses of 5, 12.5 and 20 mg/kg, subsequent to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Accumulating evidence demonstrated that the glucose‐induced oxidative stress emerged as a critical pathogenic factor in DN 4 . In addition, Sal B has been proved to be among the most effective natural antioxidants due to its polyphenolic structure 32 . Our results showed that SAL alleviated the oxidative stress in the diabetic kidneys, which was reflected by a reduction in 8‐OHdG, a marker of oxidative DNA damage as well as MDA lipid peroxidation, paralleling with augmentation of antioxidant GSH.…”
Section: Discussionmentioning
confidence: 56%
“…Accumulating evidence demonstrated that the glucose‐induced oxidative stress emerged as a critical pathogenic factor in DN 4 . In addition, Sal B has been proved to be among the most effective natural antioxidants due to its polyphenolic structure 32 . Our results showed that SAL alleviated the oxidative stress in the diabetic kidneys, which was reflected by a reduction in 8‐OHdG, a marker of oxidative DNA damage as well as MDA lipid peroxidation, paralleling with augmentation of antioxidant GSH.…”
Section: Discussionmentioning
confidence: 56%
“…SalA and SalB are the two most studied phenolic compounds in Danshen. SalA and SalB have been observed to possess a defensive effect against pathological disorders owing to their antioxidative activities [36,56,57]. SalA and SalB also exerted the therapeutic effects via the inhibition of inflam-matory response [58][59][60][61].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…The key mechanism implicated in cellular antioxidant activity is the Nrf2/HO-1/NQO1 signaling pathway [33]. Nrf2 is a redox-sensitive transcription factor that is directly activated by ROS [19,34]. Under normal circumstances, Nrf2 binds to Keap1(Kelch-like ECH-associated protein 1) and undergoes ubiquitinationdependent proteasome degradation.…”
Section: Discussionmentioning
confidence: 99%